Adoptive immunotherapy for the treatment of glioblastoma: progress and possibilities. (December 2016) - Kuramitsu, Shunichiro; Yamamichi, Akane; Ohka, Fumiharu; Motomura, Kazuya; Hara, Masahito; Natsume, Atsushi
Patients with glioblastoma have a very poor prognosis. Adoptive cellular therapy (ACT) is defined as the collection of circulating or tumor-infiltrating lymphocytes, their selection, modification, expansion and activation, and their re-administration to patients in order to induce antitumor activity. Although various ACTs have been attempted, most failed to improve the outcome. Immune checkpoint blockade antibodies and T cell engineering with tumor-specific chimeric antigen receptors suggest the emergence of a new era of immunotherapy. Here, we summarize approaches with ACTs using genetically modified T cells, which have been improved by enhancing their antitumor activity, and discuss strategies to develop these therapies. The mechanisms by which gliomas modulate and evade the immune system are also discussed.